Documenting the Social and Historical Margins in the Films of Philip Donnellan - Ieuan Franklin (Revue LISA)
This article examines the career of Philip Donnellan, an innovative BBC documentarist whose work frequently tested the boundaries of what was aesthetically and politically permissible in television documentary. For Donnellan, working-class culture was inadequately registered by the BBC, which was not only limited in its coverage but in the way it portrayed and communicated with its audience. Donnellan sought out working people and under-represented social groups: the Irish, travellers and Black migrants for instance. He created a space within his films that would allow them to speak for themselves without any overt intercession from the authorial tones and spurious objectivity of the filmmaker or the BBC. More than a document of the contemporary condition of the marginalized however, Donnellan’s films persistently convey a sense of the weight of history, exploring memory and archival evidence in order to pose difficult questions about the construction of history. In their aim to rescue the experiences of social groups from what E. P. Thompson called “the enormous condescension of posterity”, films such as Passage West (1975), The Pilgrimage of Ti-Jean (1978) and Gone for a Soldier (1980) can be compared with the Thompsonian “history from below.”